Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.2337/diacare.26.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Management in Patients With Diabetes

Abstract: OBJECTIVE -Clinical trials have demonstrated the importance of tight blood pressure control among patients with diabetes. However, little is known regarding the management of hypertension in patients with coexisting diabetes. To examine this issue, we addressed 1) whether hypertensive patients with coexisting diabetes are achieving lower levels of blood pressure than patients without diabetes, 2) whether there are differences in the intensity of antihypertensive medication therapy provided to patients with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 29 publications
3
90
3
Order By: Relevance
“…Because intense provider management may be associated with improved patient compliance, we measured diabetes management intensity (12,13). Berlowitz et al (12,13) defined diabetes treatment intensity as the likelihood of receiving an increase (increased dose, addition of a medication in another drug class, or a change of drug within the same class), decrease (lower dose, discontinuation of medication), or no change in treatment, accounting for variables believed to influence treatment decisions (e.g., HbA 1c , cholesterol levels, comorbidities). Observed changes were subtracted from these expected changes in treatment and divided by the number of visits.…”
Section: Research Design Andmentioning
confidence: 99%
“…Because intense provider management may be associated with improved patient compliance, we measured diabetes management intensity (12,13). Berlowitz et al (12,13) defined diabetes treatment intensity as the likelihood of receiving an increase (increased dose, addition of a medication in another drug class, or a change of drug within the same class), decrease (lower dose, discontinuation of medication), or no change in treatment, accounting for variables believed to influence treatment decisions (e.g., HbA 1c , cholesterol levels, comorbidities). Observed changes were subtracted from these expected changes in treatment and divided by the number of visits.…”
Section: Research Design Andmentioning
confidence: 99%
“…30,31 One prior study suggested that the complexity of simultaneously managing multiple risk factors in diabetics did not explain higher rates of TI, because increases in antihypertensive medications were no less likely for those visits in which diabetic medications were also changed. 30 In contrast, other studies on the management of chronic medical conditions in patients with comorbidities have implicated competing demands 32 and burden of comorbid illness. 33 Lack of knowledge of medical guidelines, for example, the lower BP goal in patients with diabetes or nephropathy, 34,35 probably does not explain the differences in TI in this study between patients with diabetes mellitus or nephropathy and those without.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, blood pressure control in these settings is frequently suboptimal (10 -12) and may be even worse in those with diabetes and hypertension compared with those with hypertension alone (13).…”
mentioning
confidence: 99%